1980
DOI: 10.1515/cclm.1980.18.4.237
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Histochemical Estimations of Liver γ-Glutamyltransferase Activity in Ethanol-Fed Rats

Abstract: Ethanol-fed rats showed significantly elevated plasma and liver 7-glutamyltransferase activity, compared with rats fed carbohydrates isocalorically, or with untreated control animals. The activity of-glutamyltransferase in liver was detected by means of both biochemical and histochemical methods. These data suggest that increased plasma-glutamyltransferase activity commonly found in alcoholics can be related, at least in part, to a hepatic enhancement of the activity in the liver. Biochemische und histochemisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Hepatic GGT activity after chronic ethanol feeding was observed to be increased by Ishii et al [8,12], Teschke et al [4], Teschke and Petrides [5], and Ideo et al [7], but unchanged by Morland et al [9]. In experimental studies, GGT activity was found in the microsomal fraction of the hepa- tween enzyme activités in the serum and the liver.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hepatic GGT activity after chronic ethanol feeding was observed to be increased by Ishii et al [8,12], Teschke et al [4], Teschke and Petrides [5], and Ideo et al [7], but unchanged by Morland et al [9]. In experimental studies, GGT activity was found in the microsomal fraction of the hepa- tween enzyme activités in the serum and the liver.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanisms of serum GGT elevation in alcoholics was regarded as an induction of liver GGT both of microsome and plasma membrane [4][5][6][7]21], However, experimental attempts to demonstrate this assumption us ing ethanol-fed rats have given rise to con flicting results. Hepatic GGT activity after chronic ethanol feeding was observed to be increased by Ishii et al [8,12], Teschke et al [4], Teschke and Petrides [5], and Ideo et al [7], but unchanged by Morland et al [9].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [7] re ported on the basis of histochemical observa tions that after ethanol consumption y-gluta myltransferase activity was seen on the ca nalicular membranes of periportal parenchy mal cells in addition to its normal localisa tion to the cells of the biliary tract. Previous biochemical measurements of y-glutamyl transferase activity following chronic alcohol consumption [13,14] in bile canaliculi-…”
Section: Discussionmentioning
confidence: 99%
“…GGT is synthesized in the endoplasmic reticulum of hepatocytes, transported to the plasma membranes through the Golgi apparatus and subse quently leaks into the blood and the bile [9], Histochemically GGT is normally seen in the sinusoidal membrane of the hepatocyte and in bile canaliculi, but in alcoholic livers a diffuse staining is also seen in the cyto plasm of hepatocytes [10]. Both serum and hepatic activities of GGT increase following chronic alcohol consumption [8,11,12], but the exact mechanisms responsible for this increase are not yet clear. Induction of syn thesis is probably a major factor and has been demonstrated both in vivo [ 12] and in vitro in a cultured rat hepatoma cell line [13].…”
Section: Ganima-glutamyltransferasementioning
confidence: 99%
“…Both serum and hepatic activities of GGT increase following chronic alcohol consumption [8,11,12], but the exact mechanisms responsible for this increase are not yet clear. Induction of syn thesis is probably a major factor and has been demonstrated both in vivo [ 12] and in vitro in a cultured rat hepatoma cell line [13]. However, impaired biliary secretion and hepatic clearance may also contribute [9], Certainly elevation of serum GGT pre cedes histological evidence of alcohol-in duced liver damage [14].…”
Section: Ganima-glutamyltransferasementioning
confidence: 99%